Professores de ciências do ensino fundamental II frente à implantação do currículo do estado de São Paulo/2008 - Bortoletto-Santos, Rita de Cássia (2013)
The state of São Paulo lived in 2008 the implementation of a new curriculum on state elementary and middle schools. Investigate how science teachers respond to the guidelines, challenges and dilemmas that arise and how they were solved, especially in regard to content organization, objectives, methodology and evaluation, was the concern of this work. We adopted a qualitative approach to the delivery of research, using semi-structured interviews with eight science teachers. The interviews were evaluated from the perspective of content analysis, seeking to give voice to the agents of the curriculum. It starts with the discussion about curriculum, its aims as reproductive element of ideology and power, using the idea of teacher uniqueness as a counterpoint to this perspective. This work deepens the theoretical framework using the ideas of Sacristan, especially in regard to education as a mean to a nation‟s progress, the construction of the curriculum and the relationship between the formal curriculum and the actions of teachers. Among the results, it can be noted that although the curriculum intended to regulate the teacher's work, placing him as executor, they reacted using their own knowledge when applying adjustments to what was proposed in terms of content organization and suggested strategies for classes. The idea of state schools working as a network is supported by the research subjects, which at the same time feel uncomfortable when referring to the results of SARESP or to the control from the management team of the school. Although the curriculum is justifying pedagogy skills, this perspective is not identified by teachers who resent the difficulty of engaging students in the process and point to an increase in work preparation activities. The difficulty of working with the new arrangement points to a prior culture adopted in 1975 on the teaching of science. The results are important for the development of new Public Policy Education, including teachers in their preparation, because they are shaping the prescribed curriculum, making it reality; also, they are serving as element to discuss the role of creators and universities in the curriculum proposition and teacher training.